Pengaruh Perceived Value terhadap WOM pada Produk McDonald’s saat melakukan Palestine Washing dengan Mediasi Purchase Attitude dan Loyalty - Frandiansyah, Muhammad Ilham; Lindiawati, Lindiawati (Universitas Batanghari Jambi, 2025)
This study aims to examine the effect of perceived value on WOM on McDonald's products during Palestine washing, with purchase attitude and loyalty as mediators. This study uses a quantitative approach with data collection through questionnaires distributed to respondents selected using a purposive sampling technique. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results show that perceived value has a direct and indirect effect on WOM through purchase attitude and loyalty. Purchase attitude acts as a significant mediator, where a positive purchase attitude increases consumers' tendency to spread WOM. In addition, loyalty is also an important mediator, with loyal consumers more likely to recommend McDonald's after Palestine washing. This study provides new insights for companies in managing social issue-based marketing strategies to optimize positive WOM by increasing perceived value, purchase attitude, and consumer loyalty. This study also offers a unique perspective on how global brands can build trust and remain competitive amidst the challenges of social issues.